Is there a degenerative process going on in the brain of people with schizophrenia? - Rund, Bjorn (Frontiers in Human Neuroscience, 2009)
Schizophrenia is a biological and behavioural disorder which manifests itself in neurocognitive dysfunctions. The question of whether these key characteristics of the disorder are due to schizophrenia being a degenerative disorder has been discussed for more than 100 years. Neuropsychological data indicate that neurocognitive functions are relatively stable over time after illness onset. Several studies show that there is a decline in neurocognitive functioning prior to and in connection with onset of illness. There is no convincing evidence, however, that there is a progressive neurodegenerative process after onset of illness. Morphological data, on the other hand, indicate a degenerative process. Several novel longitudinal studies indicate a rapid reduction of vital brain tissues after onset of illness. In this paper some ideas about compensatory reactions and Cognitive Reserve Theory is outlined as possible explanations of the recent MR studies that show structural changes in the brain after the onset of schizophrenia, at the same time as cognitive functioning does not become more impaired. Determining whether schizophrenia is a neurodegenerative illness with progressive structural changes in the brain after debut of the illness, or a neurodevelopmental disorder starting in early life, is of significant importance for understanding the pathophysiology of the illness and its treatments.